2020
DOI: 10.1002/pd.5767
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of prenatally diagnosed spontaneous chorioamniotic membrane separation in singleton pregnancies: A systematic review of case series and case reports

Abstract: Objectives: To provide an overview of perinatal outcomes in prenatally diagnosed spontaneous chorioamniotic separation (sCAS). Methods: A systematic search of the literature was performed from inception to July 2019, including PubMed, Ovid MEDLINE, and Ovid EMBASE. All studies reporting prenatally diagnosed sCAS after 16 weeks' gestation in singleton pregnancies were eligible. Two independent reviewers used standardized forms for data abstraction. Results: Of 408 screened abstracts, 17 studies reporting 118 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Although the incidence and the etiology of fetal death after FETO remain unclear, unexpected fetal death after FETO might occur and some cases associated with CMS may have resulted in umbilical cord compromise. Even in singleton pregnancies with spontaneous CMS, fetal death occurred in 6% of cases, with more than half of these deaths occurring due to cord strangulation 34 . CMS after FETO should be recognized as a risk factor for not only pPROM but also for an umbilical cord accident leading to fetal death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the incidence and the etiology of fetal death after FETO remain unclear, unexpected fetal death after FETO might occur and some cases associated with CMS may have resulted in umbilical cord compromise. Even in singleton pregnancies with spontaneous CMS, fetal death occurred in 6% of cases, with more than half of these deaths occurring due to cord strangulation 34 . CMS after FETO should be recognized as a risk factor for not only pPROM but also for an umbilical cord accident leading to fetal death.…”
Section: Discussionmentioning
confidence: 99%
“…Even in singleton pregnancies with spontaneous CMS, fetal death occurred in 6% of cases, with more than half of these deaths occurring due to cord strangulation. 34 CMS after FETO should be recognized as a risk factor for not only pPROM but also for an umbilical cord accident leading to fetal death.…”
Section: Discussionmentioning
confidence: 99%
“…Although in this review we were not able to comment on additional possible complications associated with iCAS, such as the risk of pseudoamniotic band formation and cord accidents, due to lack of reporting in the included studies, these concerns have been described in cases of spontaneous CAS and individual case reports following intervention 5,14,16 .…”
Section: Discussionmentioning
confidence: 99%
“…The term CAS is used to indicate detachment of the two membranes after documented fusion as evidenced by prenatal ultrasound 3,4 . A recent systematic review evaluating the outcomes of spontaneous CAS in singleton pregnancies demonstrated an increased risk for preterm delivery and a possible increase in the risk for intrauterine fetal demise, mainly due to umbilical cord accidents 5 .…”
Section: Introductionmentioning
confidence: 99%
“…There have been no previous reported cases of spontaneous chorioamniotic separation with concurrent vasa previa. Chorioamniotic separation increases significantly the risk of preterm prelabor rupture of membranes and preterm delivery [2][3][4] ; the concomitant presence of vasa previa increases the risk of severe and acute bleeding and fetal death. Despite the concern regarding perinatal mortality related to vasa previa, there are insufficient data to suggest that inpatient management reduces significantly the risk of adverse outcome 5 .…”
mentioning
confidence: 99%